Medical education in Latvia: an overview of current practices and systems - Jain, Nityanand; Jersovs, Kirils; Safina, Taira; Pilmane, Mara; Jansone-Ratinika, Nora; Grike, Ieva; Petersons, Aigars (Frontiers in Medicine, 2023)
Located in northern Europe, Latvia is one of the three Baltic States with a population of 1.9 million. The country has a rich history of medical education spanning a century and is becoming an emerging global hub for medical education. Although the surge in international students has been beneficial for the development of educational and research infrastructure, increasing demands from local students, along with institutional capacity constraints, have overburdened the available resources. Substantial investments are being made to adapt to the rapidly changing geopolitical and techno-biomedical landscape. This perspective paper presents an overview of the country’s medical education system, its challenges, and prospects from pre-university to doctoral level.